National Insight Workshop to Form Students with Nationalist Character - Lukas Sugiyanto; Dhani Agustinus; A Edi Widiargo (JPPkM: Jurnal Pengabdian dan Pemberdayaan kepada Masyarakat, 2025)
The workshop National Insights to Shape Nationalist Character in Students aimed to enhance understanding of national values and foster the nationalist character of students at Politeknik Sains Seni dan Rekreasi Bogor. Conducted over two days, the activities included presentations, discussions, simulations, and collaborative projects focusing on national pillars, the history of the nation’s struggle, and the challenges of nationalism in the digital era.The workshop results indicated an increase in students' understanding and commitment to national insights, demonstrated through creative projects and a collective declaration. This program is expected to encourage students to apply national values in their daily lives and actively contribute to maintaining the unity of the nation.